Hidden in its color: A molecular-level analysis of the beer's Maillard reaction network. (1st November 2021) - Pieczonka, Stefan A.; Hemmler, Daniel; Moritz, Franco; Lucio, Marianna; Zarnkow, Martin; Jacob, Fritz; Rychlik, Michael; Schmitt-Kopplin, Philippe
Graphical abstract: Highlights: Comprehensive picture of Maillard reaction derived chemical compositions in beer. Description of the systematic nature of Maillard reaction derived compounds. Maillard reaction molecular network in a complex food system. Experimental model validated reaction sequence analysis on a meta level. Abstract: We here report a comprehensive non-targeted analytical approach to describe the Maillard reaction in beer. By Fourier-transform ion cyclotron mass spectrometry (FT-ICR-MS), we were able to assign thousands of unambiguous molecular formulae to the mass signals and thus directly proceed to the compositional space of 250 analyzed beer samples. Statistical data analyses of the annotated compositions showed that the Maillard reaction is one of the driving forces of beer's molecular diversity leading to key compositional changes in the beer metabolome. Different visualization methods allowed us to map the systematic nature of Maillard reaction derived compounds. The typical molecular pattern, validated by an experimental Maillard reaction model system, pervades over 2, 800 (40%) of the resolved small molecules. The major compositional changes were investigated by mass difference network analysis. We were able to reveal general reaction sequences that could be assigned to successive Maillard intermediate phase reactions by shortest path analysis.